The EFL Students’ Perceptions of Literacy Activies for Students’ Interest in Reading at Senior High School - Ester Donna Simanjuntak; Erika Sinambela; Sahlan Tampubolon (Institut Agama Islam Negeri Palopo, 2023)
This study is aimed to know the EFL students’ perceptions of literacy activities for students’ interest in reading at SMA Negeri 12 Medan. A total of 265 eleventh grade students of XI P 1 until XI P 9 at SMA Negeri 12 Medan were involved in this study. This research used a descriptive qualitative design. The researcher used questionnaire technique to collect the data, the Likert Scale. The result of this research showed that most of the students’ perceptions are positive, as many as 210 (79,48%) of the 265 students, this shows that more than half of the students’ perceptions of literacy activities are positive, 127 (48,20%) students’ perceptions of students’ reading interest are positive and only 107 (40,69%) students’ perceptions of reading interest are negative. This research also showed that there are 253 (95,35%) students’ perceptions of interaction on literacy activiies for students’ interest in reading are satisfied. The frequency of students’ activities on reading and what the read affect their perception of literacy activities. Students’ literacy activities showed their interest in reading through their motivation in completing their sources for literacy activities. It can be concluded that most of the EFL students’ perception of literacy activities for students’ reading interest in Reading are positive.